2017
DOI: 10.1055/s-0036-1589066
|View full text |Cite
|
Sign up to set email alerts
|

Silver(I)-Catalyzed Deprenylation of Allylsulfonamide Derivatives

Abstract: The silver(I)-catalyzed deprenylation of sulfonamide bearing prenyl functional groups on the nitrogen atom has been developed. In this reaction, the prenyl moiety was selectively eliminated without allyl or benzyl cleavage on the nitrogen atom. In addition, geranyl was also applicable for this elimination reaction. Furthermore, sulfonamide possessing two prenyl groups underwent a double deprenylation to form the corresponding deprenylated sulfonamide. Thus, a novel reactivity between the silver cation and doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…1 H NMR (400 MHz, CDCl 3 ): δ 7.77 (d, J = 8.0 Hz, 2H), 7.31 (d, J = 8.0 Hz, 2H), 5.76–5.66 (m, 1H), 5.18–5.14 (m, 1H), 5.09–5.06 (m, 2H), 3.59–3.55 (m, 2H), 2.42 (s, 3H); 13 C­{ 1 H} NMR (100 MHz, CDCl 3 ): δ 143.4, 136.8, 132.9, 129.6, 127.0, 117.5, 45.6, 21.4. The spectroscopic data are in agreement with that previously reported …”
Section: Methodsmentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 ): δ 7.77 (d, J = 8.0 Hz, 2H), 7.31 (d, J = 8.0 Hz, 2H), 5.76–5.66 (m, 1H), 5.18–5.14 (m, 1H), 5.09–5.06 (m, 2H), 3.59–3.55 (m, 2H), 2.42 (s, 3H); 13 C­{ 1 H} NMR (100 MHz, CDCl 3 ): δ 143.4, 136.8, 132.9, 129.6, 127.0, 117.5, 45.6, 21.4. The spectroscopic data are in agreement with that previously reported …”
Section: Methodsmentioning
confidence: 99%
“…12 Solely, a single catalytic method, Ag I SbF 6mediated deprenylation of allylsulfonamides, has been reported at a very high temperature and under microwave-irradiated conditions. 13 Furthermore, a ruthenium-catalyzed C−N bond cleavage of N-propargyl sulfonamides and amides has also been reported. 14 Recently, an electrochemical method for C−N bond cleavage of secondary and tertiary N-alkyl sulfonamides has been developed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we found that the Agcatalyst (AgSbF 6 ) worked with alkenes for the cycloisomerization and deprotection reaction. 24,25) Therefore, we next examined the AgSbF 6 -catalyzed 7-endo-trig cyclization of ene-diols. The results are shown in Table 3.…”
Section: Silver Catalyst (Agsbf 6 )mentioning
confidence: 99%